Social interactions and interaction partners in infant orang-utans of two wild populations. (August 2020) - Fröhlich, Marlen; Kunz, Julia; Fryns, Caroline; Falkner, Sonja; Rukmana, Evasari; Schuppli, Mélanie; Knief, Ulrich; Utami Atmoko, Sri Suci; Schuppli, Caroline; van Noordwijk, Maria A.
Abstract : Temporary associations with conspecifics provide critical opportunities for the acquisition and development of socioecological skills, especially in species where these interaction opportunities are not readily available. In fact, social interactions can have far-reaching consequences for the cultural and communicative repertoire on both the species and population level. However, to what extent interaction rates are linked to association patterns, which depend on individual and ecological factors, is often overlooked. Here, we examined the sources of variation in immatures' social behaviour, in relation to both activity and partner type, in one Sumatran (Suaq) and one Bornean population (Tuanan) of wild orang-utans ( Pongo spp.) that are known to differ in sociability. Specifically, we examined to what extent the time spent in social interactions and with specific social partners was related to study population, but also individual (e.g. age), ecological (food availability) and social variables (e.g. presence of specific associates). Overall, we found that study population and the presence of specific associates (siblings, peers, adult males) had a profound effect on the occurrence of different social activities, while local variation in food availability did not appear to play a major role. Although proportions of time spent in interactions was overall higher at Suaq, we found no difference between the two sites regarding the use of interaction opportunities when partners were available. Begging was mainly directed at mothers, whereas peers and older siblings served primarily as play partners, and unflanged males were frequent targets of social gazing. Our study suggests that orang-utan infants use interaction opportunities differently depending on social partners and interaction type. Highlights: We examined social interactions in infant orang-utans of two wild populations. Analyses focused on three specific social activities with different partners. Study site and presence of specific associates affected interaction rates. Population differences in interaction time mirror differences in sociability.